Bargaining with Grandma: The impact of the South African pension on household decision-making - Ambler, Kate (University of Wisconsin Press, 2016)
Abstract I examine how an exogenous change in individual income affects decision-making in the household. Using the age discontinuity in eligibility for the South African pension, I find that eligible women are 15 percentage points more likely to be the primary decision-maker in the household than noneligible women. This corresponds with a large increase in their share of household income. There are no parallel effects for men. Due to labor force withdrawal, male income does not increase with eligibility, suggesting that their status in the household is unchanged.